Factors Related to Knowledge, Perception, and Practices Towards COVID-19 Among Patients with Autoimmune Diseases: A Multicenter Online Survey - Alvina Widhani; Iris Rengganis; Agus Joko Susanto; Eko E Surachmanto; Anshari Saifuddin Hasibuan; Deasy Fetarayani; Deshinta Putri Mulya; Nova Kurniati; Evy Yunihastuti; Raveinal Masri; Teguh Harjono Karjadi; Sukamto Koesnoe; et al. (Acta Medica Indonesiana, 2020)
Background: autoimmune patients can be more susceptible to infection. Proper knowledge, perception, and practices towards COVID-19 are essential for these patients during pandemic. This study aimed to know their knowledge, perception, and practices regarding COVID-19. Methods: cross sectional study using online survey was conducted from April to May 2020. Patients with autoimmune disease were asked about demographic characteristics, diagnosis, history of treatment, knowledge, perception, and practice regarding COVID-19. Results: there were 685 respondents. Most of them were female and had systemic lupus erythematosus with median age of 37 years old. Almost all respondents had good knowledge regarding transmission of COVID-19 and did proper prevention practices. Adequacy of information and steroid or mycophenolate mofetil/mycophenolic acid (MMF/MPA) use were related to perception of the effect of pandemic to their own health. Visiting private clinic and receiving hydroxychloroquine/chloroquine sulfate or sulfasalazine were related to perception that autoimmune conditions would make them more prone to COVID-19. Work from home was related to perception that when contracting COVID-19, the symptoms would be more severe. Living in Sumatra region and getting hydroxychloroquine/chloroquine sulfate or MMF/MPA were related to perception that autoimmune medications could reduce risk of getting COVID-19. Adequate information, university education, private clinic visit, and hydroxychloroquine/chloroquine sulfate use were related to perception that COVID-19 pandemic would cause difficulties in getting medications. Conclusion: almost all respondents had good knowledge and practices regarding COVID-19. Adequacy of information, autoimmune treatment, work from home, educational background, area of living, and health care facilities contributed to perception regarding COVID-19 pandemic.